Krshṇa-bhakti-kāvya kī paramparā aura Rasakhāna - Siṃha, Candralekhā, 1947- (Hindī Pracāraka Saṃsthāna, 1979)
On the tradition of Hindi devotional poetry about Krishna, Hindu deity, with special reference to Raskhan, fl. 1614; a study.